Thirty-Day Mortality in COVID-19 Positive Patients With Hip Fractures: A Case-Series and Literature Review. (4th November 2020) - Al Farii, Humaid; Al Rawahi, Salim; Samaila, Elena; Lavini, Franco; Magnan, Bruno; Al Maskari, Sultan
Introduction: The novel coronavirus has spread rapidly around the world with particularly high mortality in the elderly. Care and nursing homes have become the sites of greatest concentration of cases. We intended to review 30-day mortality of COVID-19 patients with hip fractures. This is relevant given the disease impact in this age group. Methods: Medline and Embase databases were searched for relevant studies linked to mortality and morbidity in COVID-19 patients who have undergone non-elective hip surgeries using the keywords "COVID-19"OR "SARS-cov-2"OR "Coronavirus Infections"; AND "Surgery"OR "Hip"OR "Fracture"OR "Orthopedics." We included all patients with hip fractures, but excluded pathological fractures and other non-traumatic hip pathologies. Four-hundred and eighty-one articles were identified for screening, in addition to an unpublished case-series of 67 patients that have 3 cases turned positive for COVID 19, yielding a total of 50patients for the final review. Results: The study included 4 articles published until May 9th 2020 and a case-series: 26(52%) patients were females; the median age was 86years; hypertension(53.6%), diabetes mellitus type II(28.6%), and coronary artery heart disease(25%) were the most common comorbidities; 34(68%) patients had intertrochanteric hip fracture and 16(32%) patients had femoral neck fractures; 22(59.5%) patients underwent cephalomedullary nail fixation, 12(32.4%) patients had hemiarthroplasty, and for 3(8.1%) patients, the type of surgery was not documented; 20(40%) patients died(12patients died before the surgery and 8died after surgery at a median time of 3days), 29(76.3%) patients had an unremarkable course throughout hospitalization and were discharged including 1(2.6%) patient managed non-operatively, and 1(2.6%) patient was admitted to the ICU after the surgery but eventually discharged. Conclusion: COVID-19 infected elderly patients have a higher 30-days mortality rate compared to non-COVID-19 infected cases. Further studies are warranted to look at the morbidity and mortality rates in COVID-19 positive patients with hip fractures and to investigate how these outcomes can be improved. Level of evidence: Level IV